Patent as Object of Fiduciary Guarantee in Banking Credit Practices - Bernadete Nurmawati; Dewi Iryani; Tarmudi Tarmudi (Budapest International Research and Critics University, 2022)
Intellectual property is interesting to study since it has a very important role in the advancement of the economy in this era of globalization. Intellectual Property Rights (IPR) are rights that arise from the results of the human brain's thinking that produce a product or process that is useful for the community. IPR includes intangible movable objects as regulated in article 499 of the Civil Code. This intangible object is the result of human thought and the object of ownership is a movable object that can be transferred to another party so that it can be used as a fiduciary guarantee as regulated in Law no. 13 of 2016 concerning Patents (Patent Law). Article 108 paragraph 1 states that